Near net shape structures produced by dissolvable core and plasma spraying processes - Tan, Kenneth Gim Chuan. (2009)
Free standing components have been made by spraying a coating onto a mold. Upon the solidification of the coating, a shell was formed. The shell retains the features of the external surface of the mold. After the coating has reached a sufficient thickness based on functional and strength considerations, the mold is dissolved in water. Thus, a free standing structure is formed. In today’s sophisticated surface engineering technology, thermal spraying has become an important tool used for the protection of high temperature parts. This process is commonly used in the application of solid oxide fuel cells (SOFCs). Plasma spraying, being one of the thermal spraying techniques, provides a wide range of applications in various industries. However, this process used to produce near net shape, free standing components is uncommon. Research and development work in this area is relatively rare. The advantages that plasma spraying possesses provide a good reason to examine its application in such components. Yttria-stabilized zirconia (YSZ) powder is used for the plasma spraying process. The design of dissolvable components is decided based on a few considerations. Fabrication of the three dissolvable components is accomplished by using Three-Dimensional Printing process, which is efficient and cost-saving. ZPrinter® 450 is the equipment used to carry out the process and the three components are fabricated within a short time. The materials used are starch-based and plaster-based, and they are easily washed away. A threaded rod, washers and nuts are required to hold and support the components during the plasma spraying process. Prior to the plasma spraying process, dimensional analyses are performed on the dissolvable components in order to confirm the reproducibility of the final free standing structure. Measurement of dimensions and surface roughness are done using OMIS II (6 x 12) Optical Measurement Inspection System and Talyscan 150 machine respectively. In both cases, the non-contact method is utilized. In other words, the former uses a optical comparator and integrated light to enlarge the measuring component’s profiles and features, and the latter uses a laser to scan the component’s horizontal surface. The plasma spraying process is carried out in an enclosed room using a plasma torch that is attached to the robotic arm, with most of the controls and monitors situated outside. This is due to the extreme temperatures that the process can generate. Argon and hydrogen are the working gases used together with YSZ powder. Process parameters are set prior to the commencement of the process. Safety is particularly crucial and thus, necessary steps have been taken to make sure that this project is carried out without any compromise. Results and observations gathered were not promising, but they provide a valuable step towards the research and development work in producing near net shape, free standing structures. Lastly, recommendations are given for any future work in this research area.